Kerjasama antara Biro Jasa Travel dengan Rumah Makan Perspektif Maqashid As-Syari’ah - Qinnatul Khoiroh; Wawan Juandi (Program Pascasarjana Universitas Ibrahimy, 2020)
In developing a business, a person cannot be separated from the help of others. So that other people become partners in running a business. As the case in Bintang Jaya Abadi Travel Service Agency in Banyuwangi and Ayu Lestari Restaurant in Situbondo. Both of them enter into a cooperation contract in order to promote their businesses. Bintang Jaya Abadi Travel Service Agency wants to progress with the increase in customers or enthusiasts. This is inseparable from the existence of good services and facilities. Likewise, Ayu Lestari Restaurant wants to move forward. The cooperation contract that they do is in writing. However, with other travel service agencies, restaurants also use written cooperation. The cooperation contracts they do are sale and purchase agreements and greetings (orders). The contract between them is in accordance with the shari'ah objective, namely safeguarding property (hifdz al-maal). One form of action that can keep property so that it is used for right actions is the enactment of transactions, meaning that the transactions they carry out are in accordance with the principles of Islamic law.